Adsorption of anionic polyacrylamide onto coal and kaolinite: Changes of surface free energy components. (4th March 2017) - Zou, Wenjie; Cao, Yijun; Sun, Chunbao
ABSTRACT: The wettability of floc has a large effect on the selective flocculation flotation process of fine coal separation. The changes of thermodynamic characterization of coal and kaolinite have been investigated by Washburn dynamic method and Fourier transform infrared spectroscopy (FTIR) before and after the adsorption of anionic polyacrylamide. Lipophilic hydrophilic ratio (LHR), surface free energy, and its components were calculated by Washburn equation combined with Van Oss–Chaudhury–Good theory according to the wetting curves of coal and kaolinite samples wetted by n-hexane, α-bromonaphthalene, formamide, and water. After PAM A401 adsorption, the peaks of hydrophilic functional groups of coal (the amide group, free-NH2, secondary amide N–H, C–N) were increased, while the peaks of the hydrophobic functional group, including methyl (-CH3) and methylene (–CH2–), was decreased. The LHR value of coal decreased from 9.23 to 7.28. The polar components of coal were increased, the non-polar components were decreased, and the surface free energy was increased from 39.92 to 40.43 mN m −1 . The coal surface became more hydrophilic. For kaolinite, both hydrophilic and hydrophobic functional groups were increased, while its LHR values increased from 1.44 to 1.65. The polar component was decreased from 58.27 to 55.05 mN m −2 . Results of FTIR were corresponding to the surface property.